Analysis of the Relationship Between Tourists Experience, Knowledge, Digital Strategic Decisions of Tourism Site Managers and Tourism Business Sustainability - Safrida; Elizabeth; Anindya Putri Pradiptha; Abdurohim; Lasrida Sigalingging (SEULANGA SYSTEM PUBLISHER, 2024)
The aim of this research is to propose a tourism observatory design to support strategic decision-making in tourist destinations. The proposed methodology uses input-output analysis. We propose the destination survey as a model for randomly selecting visitors at tourist attractions. The research results reveal that the observatory concept serves as a viable tool for tourism policy, addressing the information gaps at the destination level, where national statistical operations fall short. Observatories act as management tools that generate and concentrate scientific and statistical information, becoming the main source of official tourist data about a destination. However, in almost provinces, existing information does not fully meet the needs of users. Therefore, this research suggests a tourism observatory model to enhance the availability of systematic and timely information for decision-making at the provincial level. We hope that provinces and territorial units on a sub-national scale, lacking a complete tourism information system, will find the proposed model useful. We expect them to implement tourism observatory projects as a means to address specific needs, resolve local issues by uniting various tourism system participants, and address deficiencies in their current tourism statistics system. In this regard, provincial tourism observatories are expected to play a decisive role in the development of indicators and the calculation of trends, and the results obtained will provide feedback on the actions taken in relation to tourism policy.